Femtolaser Systems in Congenital Cataract Surgery in Children - I. S. Zaidullin; Yu. K. Burkhanov (Oftalʹmologiâ, 2019)
Purpose. To study the features and results of femtolaser use in congenital cataract surgery in children. Patients and Methods. 35 children (37 eyes) with congenital cataracts aged from 12 months to 14 years (5.38 ± 6.3 years) were examined and surgical treated. The first stage of the operation included femtolaser execution of the anterior capsulorhexis (femtosecond laser Victus™ (Technolas Perfect Vision/Baush&Lomb, Germany). The second stage was the flap of the anterior capsule removal, the performance of hydrodissection, aspiration of lens masses, intracapsular implantation of the IOL. Results. In case of femtolaser capsulotomy, its diameter increased. It depended on the child age and the state of the anterior lens capsule. The obtained disc diameter of the anterior capsule in almost all eyes was significantly less than planned, due to its high elasticity in children. Conclusion. The use of a femtosecond laser in children with congenital cataracts, especially in infants, increase the effectiveness of visual rehabilitation. When conducting an anterior femtolaser capsulotomy in children with congenital cataract, it is necessary to take into account an increase in the diameter of the anterior capsulotomy, depending on child age and the condition of the anterior lens capsule. The first stage of surgery under local anesthesia in older children requires an individual approach.